Normalizing acceleration and power in elite soccer with acceleration-speed profiles: A case study of game segment, position, and goal differential - Cormier, P.; Tsai, M.-C.; Klimstra, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Acceleration-speed (AS) profiling provides a novel way to quantify soccer players` maximum running ability without requiring dedicated sprint tests. This study explored how normalizing player effort with AS profiles could reveal unique patterns of changes in effort compared with nonnormalized absolute values during distinct goal differential conditions throughout matches and across positions.